2015
DOI: 10.1039/c5fd00069f
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic conversion of CO2 to produce solar fuels in electrolyte or electrolyte-less configurations of PEC cells

Abstract: The electrocatalytic reduction of CO2 is studied on a series of electrodes (based on Cu, Co, Fe and Pt metal nanoparticles deposited on carbon nanotubes or carbon black and then placed at the interface between a Nafion membrane and a gas-diffusion-layer electrode) on two types of cells: one operating in the presence of a liquid bulk electrolyte and the other in the absence of the electrolyte (electrolyte-less conditions). The results evidence how the latter conditions allow productivity of about one order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 50 publications
(85 reference statements)
0
52
0
Order By: Relevance
“…A GDL was used as the support for depositing copper because it allows operating the reduction of CO 2 with or without a liquid electrolyte. Different behaviors in CO 2 reduction could be obtained in the two cases, even using the same electrolyte, owing to different surface concentrations of CO 2 and the absence of the electrolyte in the second case . This electrode configuration allows also the introduction of elements for CO 2 capture in the GDL to enhance the surface concentration of CO 2 on the electrocatalyst, which favors the formation of >C 1 products during the electroreduction of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A GDL was used as the support for depositing copper because it allows operating the reduction of CO 2 with or without a liquid electrolyte. Different behaviors in CO 2 reduction could be obtained in the two cases, even using the same electrolyte, owing to different surface concentrations of CO 2 and the absence of the electrolyte in the second case . This electrode configuration allows also the introduction of elements for CO 2 capture in the GDL to enhance the surface concentration of CO 2 on the electrocatalyst, which favors the formation of >C 1 products during the electroreduction of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We also comment that in principle the use of in situ/operando spectroscopic methods should be used to unravel the reaction mechanism. However, we earlier showed that the formation of acetate in the electrocatalytic reduction of CO 2 is strongly dependent on the effective surface concentration of CO 2 at the electrocatalyst surface, rather than depending only on the nature of the electrocatalyst itself . In addition, changing the electrode characteristics, for example going from a GDL‐type electrode as used here to a conventional electrode, although using the same electrocatalyst, the type of species of CO 2 reduction change significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result, further commented below, well evidences that under EL-conditions, a different type of performances to those obtained under operations in the presence of a liquid electrolyte could be obtained. In a recent paper [164] the electrocatalytic reduction of CO 2 was studied on a series of electrodes on two types of cells: one operating in the presence of a liquid bulk electrolyte and the other in the absence of the electrolyte (EL-conditions). The results evidence how the latter conditions allow about one order of magnitude higher productivity and to change the type of products formed.…”
Section: Development Of the Electrocatalyst For Co 2 Reductionmentioning
confidence: 99%
“…Operations without a bulk electrolyte (electrolyte-less conditions, EL) may greatly help to develop PEC solar cells for high temperature operations [126]. Interesting indications, on both the limiting steps of the process and the reaction mechanism, have been obtained comparing CO 2 reduction performed on the same electrodes in the presence (liquid-phase) or absence (gas-phase) of a bulk electrolyte.…”
Section: Development Of Pec/artificial Leaf-type Solar Cellsmentioning
confidence: 99%